Development of a Story Book Based on The Story Telling Method for Class 3 Students of MIS Musawiyah Primary School - Sundari; Fadillah, Intan (Journal of General Education Science, 2024)
This research aims to develop storybooks based on the story telling method. This research is research and development. This research uses the Four D development model, which has four stages including define, design, develop disseminate (Wijayanti et al., 2023). This research has only reached the development stage. The research was carried out at MIS MUSAWIYAH. The research subjects were 18 class III students consisting of 11 male students and 7 female students. The object of the research is a story book based on the story telling method. The data collection techniques used are observation and tests. Data analysis techniques are (1) analysis of the feasibility of story books based on the story telling method (b) analysis of the effectiveness of story books based on the story telling method . Based on the validation results, it is known that the material validation results, namely 93.75%, are categorized as very feasible. The validation results from language experts, namely 80.00%, were categorized as adequate. Meanwhile, the validation results from media experts, namely 92.87%, were categorized as very feasible. Based on these results, it can be concluded that storybooks based on the storytelling method are said to be suitable and effective for use by grade 3 students at Mismusawiyah Elementary School.